DAMPAK KEBIJAKAN LTV TERHADAP HARGA PROPERTI BERDASARKAN PENDEKATAN SPASIAL - RIFKI KHOIRUDIN; USWATUN KHASANAH (LP2MTBM MAKARIOZ, 2022)
The LTV relaxation policy through regulation No 17 / PBI / 2015 is certainly expected to have a positive impact. With theimplementation of this policy, the public can pay a down payment for a lower mortgage to buy a house. This has an effect onthe ability to repay the community so that it has an impact on the growth of Housing Loans (KPR). In reality, there is apossibility that the impact of the LTV policy on each region may vary. This is reflected in the movement of property pricesthat can be seen from the Commercial Property Price Index. From the analysis that has been done, it can be concluded thatthe application of the Loan To Value (LTV) policy to the Residential Property Price Index (IHPR) applied on a regional basis(14 cities in Indonesia) does not have a significant effect, as well as nationally, the application of the policy LTV to IHPR hasno effect. This means that the LTV policy is inefficient to be implemented both regionally and nationally. In order to meet thehousing needs of people in Indonesia, there is a need for cooperation between the Government, the community and financialinstitutions.